Reduced nitrogen availability in hydroponically grown Chinese broccoli does not affect photosynthetic performance and yield while enhancing nitrogen use efficiency and nutritional quality - He, Jie; Tan, Wei Ling; Qin, Lin; Lai, Cheng-Hsiang; Shenhar, Itamar; Moshelion, Menachem; Ng, Kee Woei (Frontiers in Plant Science, 2026)
Nitrogen (N) deficiency negatively affects the productivity and nutritional quality of leafy vegetables. N overfertilization leads to low nitrogen use efficiency (NUE), accelerates the eutrophication of water, and may reduce productivity and nutritional quality. In this study, hydroponically grown Chinese broccoli, Kai Lan, was supplied with a gradient of six N concentrations from deficient to surplus, ranging from 40 to 400 ppm. Compared to those grown with full N of 200 ppm, plants supplied with 40 and 400 ppm N had significantly lower yield and lower photosynthetic light use efficiency and CO2 assimilation rate. However, reduced N supply at 80, 120, and 160 ppm did not affect their photosynthetic performance and final yield. Nitrate (NO3−) and total reduced nitrogen (TRN) accumulation in plants increased linearly with increasing N supply from 40 to 200 ppm. NUE was the highest at 40 and the lowest at 400 ppm N. There was no difference in nitrogen harvest index among plants supplied with 80 to 400 ppm N, which was significantly higher than plants with 40 ppm N. Reduced or excessive N did not affect leaf total soluble protein and Rubisco proteins. Leaf total ascorbic acid (ASC) concentrations were significantly lower in plants supplied with 40 and 400 ppm N compared to the other plants. For leaf total phenolic compounds (TPCs), plants grown with 40 and 400 ppm N had the highest and lowest concentrations, respectively. N-deficient treatments with 80 to 160 ppm N resulted in increased accumulation of ASC and TPC as well as dietary mineral K compared to those grown with full 200 ppm N, while the opposite trend was observed for Fe. For Mg and Ca, plants grown with 40 to 160 ppm N had similar but significantly higher concentrations than those of plants grown with full N of 200 ppm and excessive N of 400 ppm. In conclusion, it is not necessary to supply Kai Lan with full N of 200 ppm, as even though they had lower NO3− accumulation, higher nutritional quality is achieved without a yield penalty by reducing N to 120 ppm.